Laboratory Science Training Improvement Using an Immunohematology Simulation Lab - Hidalgo, Sonya (Advances in Social Sciences Research Journal, 2019)
Medical Laboratory Scientists are certified professionals who conduct assays on body fluids and other biological samples. To work in this profession one must earn a Bachelor of Science degree and complete a 12-month hospital internship. In the current state, most Medical Laboratory Science students gain their hands-on portion of their experiences in hospital laboratories. This time is severely limited, however, and can lead to inexperience upon the recent graduate beginning work. This article explores a grant-financed project to enhance the Medical Laboratory Science students’ Immunohematology experiences on campus prior to hospital experiences. The goals of this exposure are to reduce hospital errors and produce more marketable experienced graduates. This was accomplished through external grant funding, purchase of equipment and supplies, planning and management of a simulated immunohematology laboratory, and student participation in pre- and post-tests. This work was made possible through a Louisiana Board of Regents grant and the support of the College of Nursing and Health Professions at McNeese State University.